Assessment of high resolution computed tomography in the diagnosis of interstitial lung disease - Ayush, Mridul; Jakhanwal, Ishita (International Journal of Research in Medical Sciences, 2018)
Background: Interstitial lung disease (ILD) are group of pulmonary disorders characterized by inflammation and fibrosis of gas exchanging portion of the lung and diffuse abnormalities on lung radiograph. Conventional computerized tomography plays a limited role in evaluation of interstitial lung disease due to its inability to demonstrate fine parenchymal details. High Resolution Computed Tomography (HRCT) is currently the most accurate non invasive modality for evaluating lung- parenchyma. So, the purpose of the study was to assess high resolution computed tomography in the diagnosis of interstitial lung disease. Methods: 50 patients with clinical suspicion of interstitial lung disease who were referred to Department of Radio-Diagnosis and Imaging for diagnosis and evaluation were subjected to both conventional radiography and HRCT. Results: Majority of the cases i.e. 9 (18%) had honeycombing, 8 (16%) cases had crazy paving pattern and mosaic attenuation, 7 (14%) cases had miliary mottling, 6 (12%) cases had normal, 5 (10%) cases had fibrosis and ground glass haze, 2 (4%) cases had ground glass haze with Intralobular reticular opacities and 2 (4%), subpleural nodular opacities and 2 (4%) cases had B/lHilar lymphadenopathy. Conclusions: Ultimately all patients with clinical suspicion of ILDs should benefit from an HRCT scan of the thorax. High resolution computed tomography (HRCT) chest scans are essential to the diagnostic work-up since each ILD form is characterized by a specific pattern of abnormalities and a confident diagnosis can often be arrived at by HRCT alone or in correlation with the clinical symptoms. When HRCT findings are characteristic in appropriate clinical settings, HRCT may even obviate the need for a lung biopsy.